The impact of insecticides and plant extracts on the suppression of insect vector (Bemisia tabaci) of Mungbean yellow mosaic virus (MYMV). - Muhammad Younas (Public Library of Science (PLoS), 2021)
Mungbean yellow mosaic virus (MYMV) is an important constraint in successful production of mungbean (Vigna radiata L.) in many countries, including Pakistan. The MYMV spreads by insect vector whitefly (Bemisia tabaci Gennadius). The use of resistant cultivars is the most effective management tactics for MYMV. Twenty mungbean varieties/lines were screened against insect vector of MYMV under field condition in the current study. Resistance levels for varieties/lines were assessed through visual scoring of typical disease symptoms. Furthermore, the impacts of two insecticides 'Imidacloprid' and 'Thiamethoxam' and two plant extracts, i.e., neem (Azadirachta indica), and Eucalyptus (Eucalyptus camaldulensis) were tested on the suppression of whitefly. Field screening indicated that none of the tested varieties/lines proved immune/highly resistant, while significant variations were recorded among varieties/lines for resistance level. All varieties/lines were systemically infected with MYMV. The varieties 'AARI-2006' and 'Mung-14043' were considered as resistant to MYMV based on visual symptoms and the lowest vector population. These varieties were followed by 'NM-2006' and 'NL-31', which proved as moderately resistant to MYMV. All remaining varieties/lines were grouped as moderately to highly susceptible to MYMV based on visual symptoms' scoring. These results revealed that existing mungbean germplasm do not possess high resistance level MYMV. However, the lines showing higher resistance in the current study must be exploited in breeding programs for the development of resistant mungbean varieties/lines against MYMV. Imidacloprid proved as the most effective insecticide at all concentrations to manage whitefly population. Therefore, use of the varieties with higher resistance level and spraying Imidacloprid could lower the incidence of MYMV.